Computer organization and design : the hardware/software interface : ARM edition - Patterson, David A.; Hennessy, John L. (Morgan Kaufmann, 2017)
Featuring a subset of the ARMv8-A architecture, which is used to present the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies, and I/O, this book explores the emergence of mobile computing and the Cloud as well as tablet computers, Cloud infrastructure, and the ARM (mobile computing devices) and x86 (cloud computing) architectures.